2018
DOI: 10.1016/j.chempr.2017.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Correlated Protein Environments Drive Quantum Coherence Lifetimes in Photosynthetic Pigment-Protein Complexes

Abstract: Energy transfer in photosynthesis occurs as electronic excitations of coupled chromophores interact with their environment. The microscopic nature of these motions can enable novel energy-transfer mechanisms if the motions are not random. This study reveals synchronized and correlated fluctuations of the states within a photosynthetic pigment-protein complex, which explains prior observations of long-lived quantum coherence. SUMMARYEarly reports of long-lived quantum beating signals in photosynthetic pigmentp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 48 publications
(54 reference statements)
0
38
0
Order By: Relevance
“…This correlation has not been included in the theoretical considerations above. A number of studies have advocated such "environmental protection of excitonic coherence" as the source of long-lived oscillations in 2D spectra (59)(60)(61). However, no quantum mechanics/ molecular mechanics based dynamic studies of the FMO protein could identify correlations in site energy fluctuations (22,25).…”
Section: Downloaded Frommentioning
confidence: 99%
“…This correlation has not been included in the theoretical considerations above. A number of studies have advocated such "environmental protection of excitonic coherence" as the source of long-lived oscillations in 2D spectra (59)(60)(61). However, no quantum mechanics/ molecular mechanics based dynamic studies of the FMO protein could identify correlations in site energy fluctuations (22,25).…”
Section: Downloaded Frommentioning
confidence: 99%
“…At the same time, long-lived oscillatory features were observed, initially in the FMO complex 13 and later in LHCII 9 . Since then, the origin of these oscillations has been extensively debated [14][15][16][17][18][19][20][21][22][23][24][25][26] . Beyond this debate lies an even more challenging question-how does the observation of these beats spectroscopically connect to the mechanistic function of natural light-harvesting?…”
mentioning
confidence: 99%
“…Different types of the collective modes are reported to be excited in protein molecules, i.e. normal vibration modes (Acbas et al, 2014;Turton et al, 2014), sound waves (phonons) (Liu et al, 2008), and coherent vibrational states (Del Giudice et al, 1986;Rolczynski et al, 2018) which are observed on a timescale from picosecond to nanosecond. Vital cellular processes are suggested to link to the excitation of the long-lived collective degreases of freedom in macromolecules which are characterised by a weak coupling to the other ones and related to the substantially non-equilibrium processes in proteins (Mohseni et al, 2014).…”
Section: Introductionmentioning
confidence: 99%